Refining the metamemory in adulthood questionnaire: a 20-item version of change and capacity designed for research and clinical settings. (2nd July 2020) - McDonough, Ian M.; McDougall, Graham J.; LaRocca, Michael; Dalmida, Safiya G.; Arheart, Kristopher L.
Abstract: Objective: Subjective memory concerns (SMCs) might be an early indicator of future cognitive decline and conversion to dementia. However, a rich history of mixed findings, moderating factors, and heterogenous methods preclude the usefulness of SMCs in both research and clinical settings. The present study aimed to review some of the factors that might cause mixed results and propose a revised version the Metamemory in Adulthood (MIA) Questionnaire that can be easily implemented to more consistently derive estimates of SMCs. Method: We used factor analysis and regression to investigate the utility of a revised 20-item version of the MIA Change and Capacity subscales. Results: Based on two samples of older adults ( N  = 382 and N  = 221), the revised scale showed strong internal reliability and a two-factor structure. Regression analyses supported the incremental validity of the MIA-Revised Change scale in predicting performance on the Rivermead Behavioural Memory Test. Conclusions: By establishing a revised version of a well-known and previously validated questionnaire to assess SMCs, research and clinics can better implement a psychometrically sound measure quickly and easily. Moreover, the revised Change and Capacity subscales provide sufficient divergence to be sensitive to different facets of SMCs in a community dwelling older adult sample.